2020
DOI: 10.1093/conphys/coz092
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous exposure to nitrate and low pH reduces the blood oxygen-carrying capacity and functional performance of a freshwater fish

Abstract: Human activities present aquatic species with numerous of environmental challenges, including excessive nutrient pollution (nitrate) and altered pH regimes (freshwater acidification). In isolation, elevated nitrate and acidic pH can lower the blood oxygen-carrying capacity of aquatic species and cause corresponding declines in key functional performance traits such as growth and locomotor capacity. These factors may pose considerable physiological challenges to organisms but little is known about their combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 92 publications
1
21
0
1
Order By: Relevance
“…DOI: https://doi.org/10.1086/713252 kPa) and their blood-carrying capacity (lower hemoglobin concentration, HB]; and hematocrit, HCT) was marginally impaired. Exposure to other nitrogenous waste products (nitrite, ammonia) have also been shown to disrupt regular cardiorespiratory function (causing hyperventilation, tachycardia; Aggergaard and Jensen 2001; Williams et al 1997), while nitrate exposure has been shown to lower the blood-carrying capacity of various fishes via the formation of methemoglobin, and reductions in functional [HB] and HCT (Aboagye and Allen 2014;Gomez Isaza et al 2020b;Monsees et al 2017;Yang et al 2019). Indeed, in our previous study, we found that silver perch exposed to identical nitrate concentrations (50 and 100 mg NO 3 − L -1 ) experienced significant methemoglobin formation (20 -34% methemoglobin in the blood) and indicates that silver perch are susceptible long-term nitrate exposures (Gomez Isaza et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DOI: https://doi.org/10.1086/713252 kPa) and their blood-carrying capacity (lower hemoglobin concentration, HB]; and hematocrit, HCT) was marginally impaired. Exposure to other nitrogenous waste products (nitrite, ammonia) have also been shown to disrupt regular cardiorespiratory function (causing hyperventilation, tachycardia; Aggergaard and Jensen 2001; Williams et al 1997), while nitrate exposure has been shown to lower the blood-carrying capacity of various fishes via the formation of methemoglobin, and reductions in functional [HB] and HCT (Aboagye and Allen 2014;Gomez Isaza et al 2020b;Monsees et al 2017;Yang et al 2019). Indeed, in our previous study, we found that silver perch exposed to identical nitrate concentrations (50 and 100 mg NO 3 − L -1 ) experienced significant methemoglobin formation (20 -34% methemoglobin in the blood) and indicates that silver perch are susceptible long-term nitrate exposures (Gomez Isaza et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of nitrate also reduce concentrations of functional hemoglobin, lower hematocrit, and alter hemoglobinoxygen binding affinities (i.e. reduce affinity for oxygen at the gills; Gomez Isaza et al 2021; Monsees et al 2017;Yang et al 2019), effectively lowering blood oxygen carrying capacity (Gomez Isaza et al 2020b;Monsees et al 2017), raising energetic costs (Gomez Isaza et al 2018, 2020c and leading to respiratory collapse and disrupted physiological function (Jensen 2003;Jensen et al 1987). As such, organisms exposed to elevated nitrate concentrations and hypoxia are confronted with both environmental hypoxia and hypoxemia and may be unable to adequately respond to both stressors (Rodgers et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…O baixo pH é um fator ambiental capaz de aumentar a absorção de alguns poluentes causando o acúmulo desses compostos no fígado e nas brânquias (Çoǧun & Kargin, 2004). Para avaliar como o pH influencia na toxicidade do nitrato, indivíduos de Leiopotherapon unicolor foram expostos simultaneamente ao nitrato e diferentes níveis de pH (pH 4,0 ou 7,0) por 28 dias de exposição (Gomez Isaza et al, 2020). Os resultados mostraram que, a exposição ao nitrato levou ao comprometimento da capacidade de transporte de oxigênio, independentes da concentração.…”
Section: Efeitos Do Nitrato E Fatores Ambientais Que Influenciam Na Sua Toxicidadeunclassified
“…Nitrate is the most abundant nutrient contaminant globally; although less toxic than nitrite it nonetheless shows persistently high concentrations in freshwaters due to agricultural runoff from nitrogen‐based fertilizers, fossil fuel combustion, and wastewater treatment plants. Nitrate also causes the formation of methemoglobin, compromising blood oxygen‐carrying capacity (Gomez Isaza et al, 2020b). Gomez Isaza et al (2020a) investigated whether nitrate exposure would increase susceptibility to elevated temperatures, measured as CT max , and limit aerobic performance at warmer temperatures, measured as AS by swimming respirometry.…”
Section: Effects Of Contaminants On Tolerance Of Warmingmentioning
confidence: 99%
“…This absence of effects of nitrate in fish acclimated to 32°C was unexpected but paralleled the findings for CT max and aerobic performance that are reported above. In a study on the subtropical highly eurythermal spangled perch Leiopotherapon unicolor , Gomez Isaza et al (2020b) investigated effects on U crit of combinations of sublethal nitrate and low pH (acidification). The U crit was impaired by both nitrate and acid pH, with most severe impairment being in fish at the highest nitrate concentration and low pH, although the combined effect was additive rather than synergistic.…”
Section: Critical Swimming Speed As a Biomarkermentioning
confidence: 99%